Mortality, length of hospital stay, and nutritional status improvement in severely malnourished children with HIV infection in a tertiary center - Yoga Devaera (Indonesian Pediatric Society Publishing House, 2012)
Background Severe malnutrition contributes to child mortality rates, especially in children under five HIV infection further increases the risk of death. Objective To evaluate the impact of HIV infection on mortality, length of hospital stay and improvement of nutritional status in severely malnourished inpatients under five Methods This retrospective study included children aged less than 5 years and admitted to a terti ary hospital for severe malnutrition. We excluded those with incomplete data, as well as those transferred to other hospitals or discharged against medical advice. Outcome measures were live/death status, length of hospital stay and improvement of nutritional status (weight gain and improved weight􀁀for􀁀height Z score). Results Of 104 eligible patients, 97 were included as study subjects. Their mean ages were 25.8 (SD 17.3) months for HIY-infected children and 16.3 (SD 15.3) months for HIYuninfected children. Death occurred in 31.8% and 18.7% of HIV􀁀infected and uninfected subjects, respectively. Median length of hospital stay was 14.5 (range 5􀁀51) days and 11 (range 1􀁀99) days, respectively. There were no statistically significant differences in between the two groups. Weight􀁀for􀁀height Z scores (WHZ) on admission and discharge in HIV􀁀infected children were lower than those of uninfected children, but the weight gain (median weight gain of 0.45 (-0.26 to 1.9) kg vs 0.38 (-0.81 to 2.2) kg in HIV􀁀infected and uninfected children, respectively) and improvement of WHZ [1 (SD 1.1) vs 0.9 (SD 1), respectively] were similar. Conc l usion Severely malnourished children with HIV infection had higher mortality rate, and longer hospitalizations than the uninfected group, although the differences were not statistically signific ant. They also had lower mean WHZ scores at admission and discharge, butnutritionalimprovement was similar to those who were HIV􀁀negative. [Paediatr Indones. 2012;52:362-6].